THE EXISTENCE OF CORRUPTION ERADICATION COMMISSION IN THE CRIMINAL LAW REFORM IN INDONESIA - Renggong, Ruslan (Advances in Social Sciences Research Journal, 2015)
Criminal Law reform by unification and codification of the criminal law is very urgent for the need ofimprovement of sociaty. This becomes a serious problem in the offer of Law Criminal reform, as the government doesn’t pay attention to the existence of the corruption Eradication commission.As the result, inthe draft bill of the criminal code and the criminal procedural code, it is found certain subjects which cripplingthe power and the function of the corruption Eradication Commission.The crimes of corruption as the resultof the Indonesia collapse in field of economic, politic, and social before and after the reformation in 1998. It can not be solved by simple ways.It needs tobe held in a specific way.That’s, all kind of rules which will cripple the Corruption Eradication Commissionwill be revised.  The crime of corruption kept as the special crime which the basic rules of it will not be included in the criminal codeand the special power of the corruption eradicationcommission will not be ruled in the criminal procedural code, but will be ruled in the corruption eradication commission code. That the government and the newly elected representatives house membersmust revoke the draft bill of the criminal code and the criminal procedural code which has been sent to the old reperesentatives to be revised and to be adjusted with the need and the hope of the people in order to against the corruption.